1999
DOI: 10.1088/0957-0233/11/1/401
|View full text |Cite
|
Sign up to set email alerts
|

The development of a low-cost focusing probe for profile measurement

Abstract: A high-precision optical probe based on the principle of focusing-range detection is developed in this research. The probe adopted for use was directly taken from the pickup head of a CD player. Because its principle is similar to that of the autofocusing probe, the characteristics of each component of the head were investigated and its conversion into a focusing probe was attempted. The S-curve within the focusing range can be analysed, revealing the linear relationship between the normalized focus-error sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 15 publications
0
45
0
1
Order By: Relevance
“…Although the DCM lateral resolution is 1.4 times better than those of other laser probe measurement systems (LPMS), such as astigmatic method, critical angle and interferometry method [6][7][8][9], under the same conditions, its lateral resolution is still two orders of magnitude below its axial resolution. This made it very difficult for DCM lateral resolution to satisfy the stringent requirement for high LPMS spatial resolution while 3D microstructures, such as microstep, microgroove and integrated circuit line width, etc., are measured, i.e.…”
Section: Introductionmentioning
confidence: 93%
“…Although the DCM lateral resolution is 1.4 times better than those of other laser probe measurement systems (LPMS), such as astigmatic method, critical angle and interferometry method [6][7][8][9], under the same conditions, its lateral resolution is still two orders of magnitude below its axial resolution. This made it very difficult for DCM lateral resolution to satisfy the stringent requirement for high LPMS spatial resolution while 3D microstructures, such as microstep, microgroove and integrated circuit line width, etc., are measured, i.e.…”
Section: Introductionmentioning
confidence: 93%
“…It must be mentioned that, surface profiling with the DVD pickup as a sensor is not exactly a novel approach and similar research has been carried out in the past [12][13][14][15][16][17]. However, the profiles measured were 'ideal' surfaces such as CD, mirror and Silicon substrate.…”
Section: Dvd Profilermentioning
confidence: 99%
“…2. Previous studies showed that on a single material, such as DVD disk, this probe can accurately measure 3D surface to nanometer accuracy (Fan, 2000;Mastylo, 2004). Products fabricated by NEMS process are, however, mostly built up different materials on the silicon substrate.…”
Section: Focus Probementioning
confidence: 99%